How Does AI Support Child and Adolescent Psychiatry? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The mental health of children and adolescents is a growing concern worldwide. With a significant number of young people experiencing mental, emotional, or be...
Keywords: AI in Mental Health; Support; Child; Adolescent; Artificial Intelligence; Machine Learning; Healthcare